2014
DOI: 10.1186/1471-2334-14-521
|View full text |Cite
|
Sign up to set email alerts
|

A 12 week longitudinal study of microbial translocation and systemic inflammation in undernourished HIV-infected Zambians initiating antiretroviral therapy

Abstract: BackgroundUndernourished, HIV-infected adults in sub-Saharan Africa have high levels of systemic inflammation, which is a risk factor for mortality and other adverse health outcomes. We hypothesized that microbial translocation, due to the deleterious effects of HIV and poor nutrition on intestinal defenses and mucosal integrity, contributes to heightened systemic inflammation in this population, and reductions in inflammation on antiretroviral therapy (ART) accompany reductions in translocation.MethodsHIV-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 51 publications
3
5
0
Order By: Relevance
“…These findings suggest that the changes in mucosal integrity accompanying HIV infection involve permanent changes in gastrointestinal cellular function, including the loss of IL-17-and IL-22-producing cells and altered epithelial gene expression, which require time to emerge. While most studies of microbial translocation and innate immune activation in HIV infection are from developed countries, similar findings are reported from resource-limited settings [13,14].…”
Section: Cd4supporting
confidence: 63%
See 1 more Smart Citation
“…These findings suggest that the changes in mucosal integrity accompanying HIV infection involve permanent changes in gastrointestinal cellular function, including the loss of IL-17-and IL-22-producing cells and altered epithelial gene expression, which require time to emerge. While most studies of microbial translocation and innate immune activation in HIV infection are from developed countries, similar findings are reported from resource-limited settings [13,14].…”
Section: Cd4supporting
confidence: 63%
“…The combined effects of environmental factors, nutrient deficits, and HIV infection on gastrointestinal mucosal barrier defenses and microbiome composition (discussed below) contribute to increased translocation of microbes and microbial proteins into the bowel wall and circulation in malnourished HIV-infected individuals [13][14][15][16]. Microbial translocation, as measured by circulating lipopolysaccharide (LPS; a component of the bacterial cell wall), anti-endotoxin immunoglobulin M and immunoglobulin G antibodies, soluble CD14, and other biomarkers is associated with accelerated HIV disease progression and a higher risk of mortality in untreated HIV infection [17,18], although the prognostic value of these biomarkers is less clear after ART initiation [19,20].…”
Section: Malnutrition Enteropathy and Microbial Translocationmentioning
confidence: 99%
“…The enteropathy associated with HIV infection is characterized by microbial over-growth in the intestinal lumen and disrupted intestinal permeability resulting in increased levels of lipopolysaccharides (LPS) and 16S rRNA in blood plasma. Such microbial translocation most likely leads to local and systemic immune activation, characterized by increased levels of pro-inflammatory cytokines such as tumour-necrosis-factor α (TNF-α), neopterin, cluster of differentiation 14 (CD14), interleukin-8 (IL-8), and interleukin-6 (IL-6) [6], [7], [8], [9]. In particular, plasma neopterin is an established marker of monocyte activation and was repeatedly associated with HIV disease progression, greater peripheral monocyte HIV DNA reservoirs and negative neurocognitive and cardiovascular outcomes [10], [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…While the evaluation of MT biomarkers as a measure of the degree of immune activation has provided solid evidence in HIV patients from Europe or North America [5,29] it still needs further assessment in patients of African origin. Although many studies conducted in Africa reported higher levels of inflammatory markers in HIV infected individuals with respect to their seronegative counterparts [8,30,31], others found contrasting results; no correlation between HIV progression and sCD14 and LPS levels was found in Ugandan patients, that also had concentrations of sCD14 and LPS similar to those of matched seronegative Afro-American individuals [32]; similarly, a trend toward lower levels of I-FABP in HIV-positive participants compared to HIVuninfected individuals has been observed in a sub Saharan cohort, suggesting differential relationships among biomarkers of intestinal barrier integrity and innate immune activation [33]. In a recent study, our group found levels of sCD14 lower than expected in Malawian HIV pregnant women prior to ART treatment, but still associated to the immune virological parameters and to low birth weight [17].…”
Section: Discussionmentioning
confidence: 99%